Root structural aspects and development of soybean in compacted soils - Queiroz-Voltan, Rachel Benetti; Nogueira, Sandra dos Santos Sevá; Miranda, Manoel Albino Coelho de (Pesquisa Agropecuaria Brasileira, 2000)
The present study aimed at evaluating the effect of soil compaction on the root anatomy and plant development of two soybean (Glycine max (L.) Merrill) cultivars, IAC-8 and IAC-14, in pots. A clayey soil collected, from a superficial (0-200 mm) layer was used. The compaction levels consisted of 0.95 (control), 1.20, 1.35 and 1.50 kg L-1, which were obtained by compaction of some soil mass with a hydraulic press inside of iron cylinders. The soil compaction did not affect the anatomic structure of the roots, in any of the two cultivars. In the IAC-8, the leaf number, plant height and the dry matter of roots and stem decreased with the increase of soil density, and the root length was increased. In the IAC-14, the leaf number, foliar area, pod number, plant height, and weight of the dry matter of roots, stem and leaves decreased as the soil density increased, except for the intermediate densities (1.20 and 1.35), in which a trend to increase was observed in these variables. The soybean production was not affected by soil compaction, except for pod number in IAC-14, which showed differences as a function of the treatment. The results suggest that both cultivars can be well adapted to compacted soils in the analysed levels of compaction.